Abdominal ectopia cordis. About a case - Evis Johnson Montero; Juan Carlos Quintana Díaz; Raquel Rojas Bruzón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Introduction: Ectopia cordis is a rare and severe congenital malformation characterized by the displacement of the heart outside the chest cavity, there is discreet predominance in the female sex and is associated with non-potent teratogens and also related to genetic factors, its prenatal diagnosis is very important and its prognostic is unfavorable in almost all cases. Objective: Describe management with a patient with ectopia cordis at Letsholathebe Memorial Hospital II Republic of Botswana. Description: It describes the management by the pediatrician and the cardiologist from his diagnosis from birth to his hospital admissions. Conclusions: Ectopia Cordis is a rare congenital malformation that has a poor prognosis even after the surgical approach and its severity is related to the presence of other abnormalities.